Aspects of textual coherence in the writings of Al-Sakaki: Conjunctions model - Khaldi, Madjda; Lachris, Abbas (Journal of Human Sciences, 2022)
In their study of the question of separation and connection, the ancient rhetoricians did not stop at sentence boundaries alone but extended to include the study of the hierarchical relationship of sentences between them. the connection of the text can be closely related, because of its importance in the coherence of its structures, even qualified of ambiguity and accuracy combined. This is why it is necessary to know the binding sites and not to neglect them to ensure the coherence and the homogeneity of the text .... In this research, we will clarify the concept of the term coherence, and will address the question of separation and connection in Al-Sakaki’s writings and its impact on the consistency and cohesion of the text.